2021
DOI: 10.3390/math9182273
|View full text |Cite
|
Sign up to set email alerts
|

“Holographic Implementations” in the Complex Fluid Dynamics through a Fractal Paradigm

Abstract: Assimilating a complex fluid with a fractal object, non-differentiable behaviors in its dynamics are analyzed. Complex fluid dynamics in the form of hydrodynamic-type fractal regimes imply “holographic implementations” through velocity fields at non-differentiable scale resolution, via fractal solitons, fractal solitons–fractal kinks, and fractal minimal vortices. Complex fluid dynamics in the form of Schrödinger type fractal regimes imply “holographic implementations”, through the formalism of Airy functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The statistics of papers submitted to this Special Issue for both published and rejected items are as follows: 23 total submissions, of which 16 were published (69.6%) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and 7 rejected (30.4%). The authors' geographical distribution is shown in Table 1, where it can be seen that the 67 authors are from 13 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…The statistics of papers submitted to this Special Issue for both published and rejected items are as follows: 23 total submissions, of which 16 were published (69.6%) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and 7 rejected (30.4%). The authors' geographical distribution is shown in Table 1, where it can be seen that the 67 authors are from 13 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…Not only that, how this kind of structure causes nonlinearity is also delineated with the help of simulation. In the reference [18], Saviuc, A. et.al. examined the 'non-differentiability' type behavior of the mechanical system which is very much beneficial for the future research work.…”
Section: Dynamics Of Mechanical System-a Literature Reviewmentioning
confidence: 99%
“…The simulations were performed in Maple software followed by data treatment with OriginPro. The meanings of the employed quantities are the usual ones from [8,9]. The results are presented in Figure 1, where we have represented Re (F), Im (F) and F for a fixed resolution scale dependent parameter (ω) and the fractal time.…”
Section: Nonlinear Behaviors In Ablation Plasma Dynamics-numerical Si...mentioning
confidence: 99%
“…From such a perspective, various operational procedures such as group invariants, joint invariant functions, Riemannian type differential geometries, parallel transport of directions in the Levi-Civita sense, harmonic mappings from the usual space to the hyperbolic one become functional in the description of the dynamics of various complex systems. For instance, in the recent papers [8][9][10], assimilating any complex system with a multifractal mathematical object, non-differentiable behaviors of complex systems are analyzed. Then in-phase coherence of the dynamics of any complex system structural units, which implies, for example, special cubics with SL(2R)-type group invariance, special differential geometry of Riemann type associated to such cubics, special apolar transport of cubics assimilated with parallel transport of direction in Levi-Civita sense, special harmonic mapping imposed by means of parallel transport of direction, etc., make possible various scenarios to chaos (period doubling, intermittences, etc.…”
Section: Introductionmentioning
confidence: 99%